Penerapan Model Project Based Learning Dalam Meningkatkan Hasil Belajar IPA Siswa Di SD Kelas VI - Andika, Rivaldi (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2025)
The aim of this research is to improve the science learning outcomes of class VI students at UPT SD Negeri 19 Toro by implementing the Project based learning model. This type of research is Classroom Action Research (PTK) carried out in 2 cycles. Data collection uses test and non-test, data is analyzed using descriptive techniques. The research subjects were 12 students in class VI UPT SD Negeri 19 Toro. The results of the research show that cognitive learning outcomes in the pre-cycle of student learning completeness were 42%, then increased by 74% in Cycle I and increased again in Cycle II, amounting to 100% student learning completeness. The students' psychomotor results experienced an increase, in cycle I the value of the product assessment aspect had an average value of 80 with a percentage of 100% and in cycle II the average increased to 84 with a percentage of 100%, the percentage assessment in cycle I had an average value of 77% with a percentage of 84% in cycle II the average increased to 83 with a percentage of 100%. The research results can be concluded that the application of the Project Based Learning (PJBL) model can improve science learning outcomes